Low-grade lymphomas. Expression of developmentally regulated B-cell antigens. - Cossman, J. (1984)
A series of low-grade B-cell lymphomas was analyzed for a battery of immunologic determinants by flow cytometry and immunohistochemistry. Histologically distinctive subclasses of these lymphomas, well-differentiated lymphocytic (WDL), intermediately differentiated lymphocytic (IDL), and follicular center cell (FCC) lymphoma, were found to be readily distinguishable by their expression of immunologic determinants that are known to be developmentally regulated in normal B cells. Although all cases expressed monoclonal surface immunoglobulin (sIg), HLA-DR, and the surface membrane proteins recognized by antibodies B1 (p32) and BA1, staining with other monoclonal antibodies revealed unique immunologic phenotypes for each subclass: WDL p65 (Leu 1)+, p24 (BA2)-; IDL p65+, p24+; FCC p65-, p24-. Additionally, the fluorescence intensities (number of determinants per cell) obtained for sIg, BA-1, and B1, but not HLA-DR, were significantly different among the three lymphoma subclasses. The relative fluorescence intensities of each of these three markers followed the same pattern: FCC greater than IDL greater than WDL. Taken together, these distinguishing features suggest that low-grade B-cell lymphomas represent arrested, and possibly sequential, stages of B-cell differentiation.